Mythologies of evil and the glory of Ethiopia in the Kǝbrä nägäśt - Binyam, Yonatan (Journal for the study of the pseudepigrapha, 2025)
This article traces a number of overlapping themes related to the origins of evil that are present in certain Jewish and Christian pseudepigraphic texts, the Quran, and the Gǝ‘ǝz (or Ethiopic) Kǝbrä nägäśt. The Kǝbrä nägäśt features a mythology of evil that conflates different narratives about how evil was introduced into the world. In particular, the Ethiopic work brings together narratives about the fall of the angels in the Book of the Watchers in 1 Enoch with stories about the fall of Satan as related in pseudepigraphic texts like the Life of Adam and Eve and the Apocalypse of Moses. An expansion of the biblical account of Adam and Eve in Genesis can also be found in the Quran, which expounds on the motivations that led Satan to rebel against Allah. One finds echoes of these various themes in the mythology of evil in the Kǝbrä nägäśt, which I argue not only evinces a number of entanglements between different scriptural and parabiblical traditions, but is also thematically linked to the glorification of Ethiopia over Israel as the new location of the glory of Zion.